Respon Pertumbuhan dan Hasil Kedelai Varietas Anjasmoro Terhadap Pemberian Bokashi Serabut Buah Kelapa Sawit - Muhammad Arifin; Chatimatun Nisa; Zuraida Titin Mariana (Agroekotek View, 2018)
Decreasing of production soybean caused by low soil fertility with supply organic fertilizer can increase soil fertility, decrease toxic environment from using chemist fertility. Organic fertilizer from fibers oil palm contain 0,32% Nitrogen; 0,08% Phosfor; 0,47% Potassium; 0,02 Magnesium and 0,11 Calcium. This research is an experiment conducted in the bed by using (RAL) one factor with 6 treatment, 5 replication and 30 unit experiment. The treatment consists of a). Control (0 ton/ha) b). 5 ton/ha c). 10 ton/ha d). 15 ton/ha e). 20 ton/ha and f). 25 ton/ha fibers palm oil of bokashi. 25 ton/ha fibers palm oil of bokashi increased supply for wet seed and dry seed weight of soybean. Treatment 5, 10, 15, 20 and 25 ton/ha fibers palm oil of bokashi not significant for availability N dan K in soil of 2 weeks incubation, but significant for availability P in soil. 20 ton/ha fibers palm oil of bokashi supply availability P to upper.